ANALYSIS OF THE LEVELS OF CONPETÊNCIA DRIVING POPULATION OF PRIMARY SCHOOL STUDENTS FROM CATALONIA, ACCORDING TO THE STUDY OF PRIOR SKILLS IN PHYSICAL EDUCATION (Fiep Bulletin - online, 2011)
This research project, from a study of skills in physical education, aims to analyze the level of driving competence of students in the final stage of primary education, the educational system in Catalonia. It is to know the current situation on the power motive in the context above, by applying a battery power, which will cover the four specific skills in the physical education curriculum determined by the LOE. This study provides indicators that will build a profile of knowledge and motor skills of children of primary school. The results of this research, presenting the problems and results, will make possible the construction of programs for prevention and intervention.
Keywords: Physical Education; Skills; Driving Evaluation